Pendidikan Kesehatan Tentang Tanda Bahaya Kehamilan Pada Ibu Hamil Di Desa Binaan - M, Warda; Yakob, Asmirati; Rahmat, Rezqiqah Aulia (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Health education is a form of promotive and preventive intervention to reduce maternal morbidity and mortality. Knowledge of pregnancy danger signs is crucial for early detection and prompt medical attention if complications arise. This community service activity aims to increase the knowledge of pregnancy danger signs among pregnant women in the assisted villages. The methods used were lectures, interactive discussions, and distribution of leaflets to 35 pregnant women in the assisted villages. Evaluation was conducted through pre- and post-tests. The results showed an increase in knowledge from 48.6% (sufficient category) in the pre-test to 85.7% (good category) in the post-test. This activity is expected to increase pregnant women's awareness of maintaining a healthy pregnancy and taking early steps to prevent complications.